Selecting effective colors for high-visibility safety apparel - Mina, Achilleas; Lanitis, Andreas; Dimitriou, Pavlos Alexandros; Partaourides, Charalampos; Pericleous, Pericles (My University, 2021)
The proper use of high-visibility safety apparel (HVSA) increases conspicuity and reduces accident rates. The main factor affecting daytime conspicuity is the color contrast between HVSA and the ambient background environment. Selecting HVSA without considering their contrast to the worksite environment may result in unsafe situations where HVSA not only fail to provide the desired conspicuity but also act as camouflage. One such situation is the use of red HVSA on oil tankers with brown decks. This paper presents a methodology for selecting the most effective HVSA color for a particular worksite. Using image analysis techniques, we can assess the contrast between a set of high-visibility colors and the colors present at a worksite in order to determine the most effective HVSA color for the particular site. The methodology was experimentally validated with the help of 50 volunteers and the use of a purpose-built validation software. Results showed a 27% reduction in the time required to detect workers when the color of their HVSA was changed to match the color determined as per the proposed methodology.
Keywords: Conspicuity; Personal protective equipment; Workplace Intervention; High-visibility vest; Visibility aids; Occupational safety